PENGARUH KOMITMEN ORGANISASI, KOMPETENSI DAN SISTEM AKUNTANSI INSTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN ETIKA SEBAGAI VARIABEL MODERASI (SETUDI EMPIRIS PADA BADAN PUSAT STATISTIK PROVINSI RIAU) - Fitrisyah, Aidil; M. Rasuli, M. Rasuli (Jurnal Tepak Manajemen Bisnis, 2017)
This study to determine the direct influence of organizational commitment,competence and Instance Accounting System to the quality of financial Reporting. Andthe indirect influence of organizational commitment, competence and InstanceAccounting System to the quality of financial Reporting with ethics as a moderationvariable at BPS Provinsi Riau.The result of the research is first direct influence,organizational commitment have a positive effect to the quality of financial Reportingwith significance value equal to 0,046, the competence have positive effect to the qualityof financial Reporting with significance value equal to 0,028 and Instance AccountingSystem have positive effect to quality of financial Reporting with significance valueequal to 0,033. Both indirect influences, organizational commitment strengthened ethicseffect on the quality of financial Reporting with a significance value of 0.037, ethicalstrengthened competence affect the quality of financial Reporting with a significancevalue of 0.043 and Instance Accounting System is weakened ethics does not affect thequality of financial Reporting with a significance value of 0.135.